Is endometriosis typology a potentially better classification system for assessing risk of female infertility? - Karen C. Schliep, Ph.D.; Anna Z. Pollack, Ph.D.; Leslie V. Farland, Sc.D.; May Shaaban, M.P.H.; Bin Yan, M.S.T.A.T.; Jing Wang, Ph.D.; Lina Ghabayen, M.D.; Rachael B. Hemmert, M.S.P.H.; Joseph B. Stanford, M.D.; C. Matthew Peterson, M.D. (F&S Reports)
Objective: To determine whether endometriosis typology, namely ovarian endometriomas (OE), deep infiltrating endometriosis (DIE), or superficial endometriosis (SE), correlates with fertility history. Design: Prospective cohort. Setting: One of fourteen surgical centers in Salt Lake City, Utah (n = 5) or San Francisco, California (n = 9). Patient(s): A total of 473 women (18–44 years) with no prior endometriosis diagnosis, undergoing laparoscopies/laparotomies, irrespective of indication, in Utah or California (2007–2009). Exposure: Incident endometriosis. Main Outcome Measure(s): Before surgery, we queried women about time to become pregnant for prior planned pregnancies. Generalized linear models were used to calculate adjusted prevalence ratios (aPR) for association between endometriosis typology and infertility, defined as having ever tried >12 months (>6 months for women ≥35 years) to get pregnant. We also generated fecundability odds ratios (aFOR) to capture time to pregnancy. Result(s): Twenty-five percent (n = 116) of women were diagnosed with SE only, 5% (n = 23) with OE, 6% (n = 29) with DIE, and 5% (n = 22) with OE + DIE, and 60% (n = 283) with no endometriosis. Compared with women with no endometriosis, women with SE had a 1.58 higher aPR (95% confidence interval [CI], 1.16–2.14), although women with OE and/or DIE had a 2.41 higher aPR for subfertility after adjusting for women’s age, body mass index, and site. Compared with women with no endometriosis, women with OE and/or DIE had a 53% lower historic fecundability (aFOR, 0.47; 95% CI, 0.24–0.95); however, no association was found among women with SE (aFOR, 0.81; 95% CI, 0.49–1.33). Conclusion(s): Specific endometriosis typologies may be associated with fecundability, with OE and/or DIE associated with nearly a 150% higher prevalence of subfertility and over a 50% lower historic fecundability.